Influence of good corporate governance and the sharia supervisory board on the financial performance of sharia banking in Indonesia - Swadia Gandhi Mahardika; Akbar Lufi Zulfikar (Institute of Computer Science (IOCS), 2024)
This research aims to discuss and analyze the internal mechanisms of good corporate governance such as: the influence of the effectiveness of the audit committee on the performance of the Islamic banking system, the influence of the effectiveness of the risk supervision committee on the performance of the Islamic banking system, and the influence of remuneration and committee appointments on the performance of the Islamic banking system. sharia banking operations, as well as the effectiveness of the sharia supervisory board on the operations of the sharia banking system in Indonesia during the 2022 period. The data used in this research is secondary data obtained by measuring the number of meetings held for each variable. The method used to select samples was purposive sampling. The sample size in this study was six banks taken from annual reports, with a sample size of 30 people. The hypothesis test used in this research is the t-statistical test. The data analysis technique used in this research is multiple linear analysis using Statistical Products and Services Solutions (SPSS) version 26.0. The research results show that the effectiveness of the sharia supervisory board has a positive effect on sharia financial performance.